Oscillation-Based Spectroscopy for Cell-Culture Monitorization - Pérez, Pablo; Serrano-Viseas, Juan A.; Fernández-Scagliusi, Santiago; Martín-Fernández, Daniel; Huertas, Gloria; Yúfera, Alberto (Frontiers in Electronics, 2022)
Biological Impedance is a physical property related to the state and inherent evolution of biological samples. Among the existing impedance measurement methods, Oscillation-Based (OB) tests are a simple and smart solution to indirectly measure impedance correlated with the amplitude and frequency of the generated oscillation which are proportional to the sample under test. An OB test requires tuning of the system blocks to specifications derived from every measurement problem. The OB setup must be done to obtain the optimum measurement sensitivity for the specific constraints imposed by the system under test, electronic interfaces, and electrodes employed for test. This work proposes the extension of OB measurement systems to spectroscopy test, enabling a completely new range of applications for this technology without the restrictions imposed by setting a fixed frequency on the electrical oscillator. Some examples will be presented to the measurement of cell cultures samples, considering the corresponding circuit interfaces and electric models for the electrode-cell system. The proposed analysis method allows the selection of the best oscillator elements for optimum sensitivity range in amplitude and frequency oscillation values, when a specific cell culture is monitored for the OB system.